Kinetics of Oxidation of 3-Benzoylpropionic Acid by N-Chlorobenzamide in Aqueous Acetic Acid Medium - N. A. Mohamed Farook; G. A. Seyed Dameem (E-Journal of Chemistry)
The kinetics of oxidation of 3-benzoylpropionic acid (KA) by N-chlorobenzamide (NCB) in aqueous acetic acid medium in the presence of perchloric acid have been investigated. The observed rate of oxidation is first order dependence each in [KA], [NCB] and [H+]. The main product of the oxidation is the corresponding carboxylic acid. The rate decreases with the addition of benzamide, one of the products of the reaction. Variation in ionic strength of the reaction medium has no significant effect on the rate of oxidation. But the rate of the reaction is enhanced by lowering the dielectric constant of the reaction medium. Hypochlorous acidium ion (H2O+Cl), has been postulated as the reactive oxidizing species. A mechanism consistent with observed results have been proposed and the related rate law deduced. The activation parameters have been computed with respect to slow step of the mechanism.